Nmap essentials harness the power of Nmap, the most versatile network port scanner on the planet, to secure large scale networks - Shaw, David (Packt Publishing, 2015)
Nmap is an extremely powerful network port scanner used to identify hosts on a network. Nmap is free, flexible, powerful, and easy to implement, which makes it a very convenient utility. This book demonstrates how to run basic and advanced scans, optimizing them to perform well in a variety of environments. Starting with an overview of Nmap, the reader will be guided through installation on popular operating systems. The book then explains how to use Nmap to run basic and advanced scans in addition to using the Nmap Scripting Engine (NSE). All this helps with optimizing Nmap performance in a variety of environments, eventually enabling the reader to integrate with other Nmap tools such as Nessus, Nikto, Burp Suite, and NSE versus NASL scanning. By the end of the book, the reader will have gained essential insights into network security analysis.
Includes index. - Online resource; title from cover (Safari, viewed June 10, 2015)
Keywords: Computer networks -- Monitoring -- Computer programs; Computer networks -- Security measures -- Computer programs; Réseaux d'ordinateurs; Surveillance; Logiciels; Réseaux d'ordinateurs; Sécurité; Mesures; Logiciels; Informatique; data processing; computer science; COMPUTERS; Networking; Network Protocols; COMPUTERS; Networking; General; Computer networks; Security measures; Computer programs; Instructional and educational works; Matériel d'éducation et de formation